Evaluasi keberadaan ruang terbuka hijau di Kecamatan Tangerang, Kota Tangerang, Banten - Ardila, Siti; Budiyanti, Rully Besari; Suryanti, Titien (Jurnal Arsitektur Lansekap, 2020)
Tangerang City is one of the cities in the Tangerang region which is known as a city of a thousand parks with various types and functions. Tangerang City is consists of 13 sub-districts, one of them is Tangerang SubDistrict that has an area of 17,45 km² based on land use Tangerang Sub-District is has a more diverse and wider green open space and as an ecologically is.complete for all aspect in landscape structure compared to other sub-districts. Landscape structure is an arrangement of landscape elements consisting of green open spaces in form of corridors as the green belt along the river, the green belt along the railroad, matrix as soccer field, network as the green belt along the way, and patches as road island (Godron, 1963: 83). Although as an ecologically is complete.compared to other sub-districts, however, the Spatial Planning requires 30% and the area is green open space. For this reason, it is necessary to evaluate the existence of green open space, evaluation is done as an effort to achieve the goal of forming a system of green open space as an effort to increase the percentage of green open space to 30% of the total area. This research was conducted with a qualitative approach, while the qualitative stage is to evaluate the fulfillment of the criteria and each of the mapped green open spaces. Data collection is done by survey methods in the form of observations, questionnaires and interviews, whereas to do data analysis using the assessment method, which is often done to evaluate the existence of green open space (Besari, 2014).